2012
DOI: 10.1136/gutjnl-2011-301647
|View full text |Cite
|
Sign up to set email alerts
|

Scheduled endoscopic surveillance controls secondary cancer after curative endoscopic resection for early gastric cancer: a multicentre retrospective cohort study by Osaka University ESD study group

Abstract: Nineteen per cent of synchronous cancers were not detected until the initial ESD. The incidence rate of metachronous cancer after ESD was constant. Scheduled endoscopic surveillance showed that almost all recurrent lesions were treatable by endoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
210
4
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(233 citation statements)
references
References 21 publications
14
210
4
5
Order By: Relevance
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported annual incidences of MGC after H. pylori eradication, ranging from 0.1 to 0.5 % in healthy individuals or peptic ulcer patients [26][27][28][29][30][31][32][33], and from 0.8 to 4.1 % in patients after endoscopic resection for early gastric cancer [9,[11][12][13][14][15]. Individuals after endoscopic resection had a higher risk of MGC compared with those who were healthy or had peptic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…A previous multicenter prospective randomized study performed in Japan showed that eradication of Helicobacter pylori reduced the incidence of MGC after endoscopic resection for early gastric cancer [11]. However, MGC sometimes develops even after successful H. pylori eradication, with an annual incidence of 0.8-4.1 % [9][10][11][12][13][14][15]. In most previous studies, only incidences of MGC within a 3-year median follow-up period were reported, and a study with a longer follow-up period is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Kato et al reported that synchronous early gastric cancer had a prevalence of approximately 9%. 24 One possible reason for the risk of synchronous lesions is the endoscopist's lack of experience. Therefore, careful preoperative examination by an experienced endoscopist is needed.…”
Section: Elderly Patients N=130mentioning
confidence: 99%
“…A multicentre retrospective cohort study from 12 hospitals aimed at elucidating the time at which multiple GCs develop and determining whether scheduled endoscopic surveillance might control their development [13]; 1258 Japanese patients with early GC (EGC) who underwent endoscopic submucosa dissection (ESD) with en bloc margin-negative curative resection from April 1999 to December 2010 were included. Synchronous cancer was classified as concomitant cancer or missed cancer.…”
Section: Gastric Cancer: Secondary Preventionmentioning
confidence: 99%